Hubungan Pesan Moral dalam Lagu Beyond The Scene (BTS) dengan Sikap Penggemarnya - Sarah Aprilia Lukman; Ratri Rizki (Bandung Conference Series: Journalism, 2022)
Abstract. Many musicians make a song with various messages implied in it, one example is a boy band from South Korea with hundreds of millions of fans from various countries, namely Beyond The Scene or familiarly called BTS. It is undeniable that the attitude of a time has a correlation with the song being listened to. In accordance with the identification of the problem, this study aims to see how the moral message in BTS songs through prosocial and anti-social aspects relates to the attitude of BTS fans, namely ARMY. This research uses correlational study method. Data collection techniques were carried out by distributing questionnaires, literature studies and online data searches. To dissect this research, mass communication, cognitive psychology theory, S-O-R theory and social cognitive theory are used. The respondents in this study were ARMYs in Indonesia. Sampling using the Slovin formula and obtained as many as 99 respondents. In testing the validity and reliability of the questions for distributing the questionnaire, it can be said to be valid and reliable. The results in this study are there a significant relationship between the moral message in the BTS song Permission to Dance with the social attitudes of Adorable Representative MC For Youth (ARMY) in Indonesia. Abstrak. Banyak musisi membuat suatu karya lagu dengan berbagai macam pesan yang tersirat di dalamnya salah satu contohnya boyband asal Korea Selatan dengan ratusan juta penggemar dari berbagai macam negara yaitu Beyond The Scene atau akrab disebut BTS. Tidak dipungkiri sikap suatu waktu mempunyai korelasi dengan lagu yang didengarkan. Sesuai dengan identifikasi masalah, penelitian ini bertujuan untuk melihat bagaimana hubungan pesan moral dalam lagu BTS melalui aspek Prososial dan Anti Sosial dengan sikap para penggemar BTS yaitu ARMY. Penelitian ini menggunakan metode studi korelasional. Teknik pengumpulan data dilakukan dengan cara menyebarkan kuesioner, studi pustaka dan penelusuran data online. Untuk membedah penelitian ini digunakan teori komunikasi massa, teori psikologi kognitif, teori S-O-R dan teori kognitif sosial. Responden yang menjadi penelitian ini adalah ARMY yang berada di Indonesia. Pengambilan sampel menggunakan rumus slovin dan didapatkan sebanyak 99 responden. Pada uji validitas dan reliabilitas pertanyaan untuk penyebaran angket dapat dikatakan valid dan reliabel. Hasil dalam penelitian ini adanya hubungan yang signifikan hubungan antara pesan moral dalam lagu BTS Permission to Dance dengan sikap sosial penggemarnya Adorable Representative MC For Youth (ARMY) di Indonesia.